Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan (Kasus Pelanggan Indosat Ooredoo) - Muhammad Halilintar; Siti Maryam Litikasuri MS (Fakultas Ekonomi Universitas Borobudur, 2020)
The purpose of this study was to determine the effect of product quality, service quality andprice on customer satisfaction of telecommunication operators Indosat Ooredoo in CengkarengBarat, West Jakarta. This research was conducted using a data collection method by means of aquestionnaire on 100 respondents of Indosat Ooredoo card users in the Cengkareng Barat area,West Jakarta. The sample was taken using the proportion estimation formula. Testing data qualityin this study using validity and reliability tests. Data were analyzed using multiple linearregression analysis.The results showed that the variable product quality partially / partially has an influence oncustomer satisfaction, this is evidenced by the t test with a t-count value of 2.353. Service qualityvariable partially / partially has an influence on customer satisfaction, this is evidenced by the ttest with a t-count value of 2.105. The price variable partially / partially has an influence oncustomer satisfaction, this is evidenced by the t test with a t-count value of 8.664. The variables ofproduct quality, service quality and price as a whole have an influence on customer satisfaction,this is evidenced by the F test with an Fcount of 76.400.Keywords: Product Quality, Service Quality, Price, Multiple Linear Regression Analysis